The third love : a novel - Kawakami, Hiromi, 1958- (Soft Skull, 2025)
"Having married her childhood sweetheart, Riko now finds herself trapped in a relationship soured by infidelity. One day, she runs into her old friend Mr Takaoka, who offers friendship, love, and an unusual escape: he teaches her the trick of living inside her dreams. Now, each night, she sinks into another life: first as a high-ranking courtesan in the seventeenth century, and then as a serving lady to a princess in the late Middle Ages. As she experiences desire and heartbreak in the past, so Riko comes to reconsider her life as a twenty-first-century woman-as a wife, as a mother, and as a lover-and to ask herself whether, after loving her husband and loving Mr Takaoka, she is ready for her third great love"-- Provided by publisher.